Development and Performance Testing of a PANI–GO Soil Conductivity Sensor - Nuralam Nuralam; Rizdam Firly Muzakki; Sri Lestari Kusumastuti; Hariyanto Hariyanto (Jurusan Teknik Elektro UIN Sunan Gunung Djati Bandung, 2026)
Smart agriculture systems require soil sensors capable of monitoring environmental conditions in real-time and with high accuracy. This research presents the design and fabrication of a soil conductivity sensor prototype using a composite material of Polyaniline (PANI) and Graphene Oxide (GO). The prototype is designed with a two-electrode structure based on copper layers, where the active PANI–GO layer functions as a conductive path that responds to soil moisture and ion levels. The PANI–GO composite was synthesized through a polymerization method and then applied to copper-based electrodes. Test results showed detectable changes in resistance according to variations in soil moisture content, where resistance values decreased as the soil became moister and more fertile. Moisture levels were adjusted to 10%, 20%, 30%, and 40% for two soil types: fertile and infertile. These results indicate the potential of the composite material as a simple soil sensor that can be further developed for Internet of Things (IoT) applications in agriculture. This study serves as a foundational step in the development of low-cost, flexible, and easily integrated conductive soil sensors.